2019
DOI: 10.3390/ijerph16152773
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Dental Sealant Use and Caries Prevalence Affected by National Health Insurance Policy Change: Evidence from the Korean National Health and Nutrition Examination Survey (2007–2015)

Abstract: We evaluated the effect of the National Health Insurance (NHI) policy including dental sealant on changes in the prevalence of sealant and caries, and examined how NHI affected sealant utilization and untreated caries in children from diverse income groups in South Korea. We used a multivariate logistic regression analysis to explore the effects of three stages of dental sealant policy (pre-policy: 2007–2009, first post-policy: 2010–2012, and second post-policy: 2013–2015) on the prevalence of dental sealant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…After the coverage expansion of dental sealants, the prevalence of untreated dental caries decreased and that of having sealant treatment increased in both children and adolescents. This study also showed an overall increase in dental service usage after the coverage expansion [17]. A similar review on smoking inequality in youth after tobacco control policies concluded that [40] education and information communication led to widening inequalities, while the tobacco price policy reduced socioeconomic inequalities.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…After the coverage expansion of dental sealants, the prevalence of untreated dental caries decreased and that of having sealant treatment increased in both children and adolescents. This study also showed an overall increase in dental service usage after the coverage expansion [17]. A similar review on smoking inequality in youth after tobacco control policies concluded that [40] education and information communication led to widening inequalities, while the tobacco price policy reduced socioeconomic inequalities.…”
Section: Discussionsupporting
confidence: 59%
“…Based on the review of the effects of public health policies on health inequalities, Thomson et al [42] concluded that two types of oral health interventions had positive effects on inequalities: water fluoridation [43] and a national tooth brushing education campaign [44]. Another study pointed out that dental insurance is an important driver for dental service use, as tackling financial barriers mostly reduces unmet dental needs [17,45]. US studies to examine the effects of the Children's Health Insurance Program also reported an increase in sealant treatment, fluoride tablets, and dental visits and a decrease in untreated caries since 1997, especially in children from lower-income households who benefited from free or subsidized school lunch programs [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the coverage expansion of dental sealants, the prevalence of untreated dental caries decreased and that of having sealant treatment increased in both children and adolescents. This study also showed an overall increase in dental service usage after the coverage expansion [17]. A similar review on smoking inequality in youth after tobacco control policies concluded that [38] education and information communication led to widening inequalities, while the tobacco price policy reduced socioeconomic inequalities.…”
Section: Discussionsupporting
confidence: 59%
“…Accordingly, the proportion of children aged 6-14 years who received dental sealant increased encouragingly, from 28.7-34.9% [16]. A Korean study reported that after the policy implementation, dental sealant increased and untreated caries decreased, especially among lower SEP groups [17]. Many existing studies have suggested that equal access to dental treatment is essential to improve the dental status of all [18].…”
Section: Introductionmentioning
confidence: 99%